2007
DOI: 10.1002/ange.200701194
|View full text |Cite
|
Sign up to set email alerts
|

The Geometric and Electronic Structure of a One‐Electron‐Oxidized Nickel(II) Bis(salicylidene)diamine Complex

Abstract: The cooperativity of transition-metal ions and proradical ligands in metalloenzyme active sites is of current research interest. [1] In an effort to understand the intricacies of the interaction of metal ions with organic radicals, many transition-metal complexes with one or more organic radical ligands have been studied. [2][3][4] Depending on the relative energies of the redox-active orbitals, metal complexes with proradical ligands can exist in a limiting description as a metal-ligand-radical (M n+ (LC)) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
52
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 35 publications
12
52
0
Order By: Relevance
“…[9,14] The CV curve for 2 exhibits two closely-spaced reversible one-electron redox couples at E 1 1=2 = 360 mV and Table 3. [9,14] The CV curve for 2 exhibits two closely-spaced reversible one-electron redox couples at E 1 1=2 = 360 mV and Table 3.…”
Section: Results and Analysismentioning
confidence: 93%
See 2 more Smart Citations
“…[9,14] The CV curve for 2 exhibits two closely-spaced reversible one-electron redox couples at E 1 1=2 = 360 mV and Table 3. [9,14] The CV curve for 2 exhibits two closely-spaced reversible one-electron redox couples at E 1 1=2 = 360 mV and Table 3.…”
Section: Results and Analysismentioning
confidence: 93%
“…The proradical tyrosine ligand acts as an additional redox cofactor, facilitating electron transfer during catalysis. [8][9][10] One area of recent focus are tetradentate salen ligands (salen is a common abbreviation for N 2 O 2 bis-Schiff-base bis-phenolate ligands). [3,5,6] Recent interest has centered on the design of synthetic systems that employ the cooperative effect of redox-active ligands to drive new catalytic processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…with two imino and two phenolate groups in the coordination sphere of the metal ion. [2,3,40] We observed, in contrast with the phenol containing ligands, a distinct difference in the spin density distribution map. As can be seen in Figure 7, the contribution of the imidazolate rings is very weak in the description of the SOMO (a HOMO).…”
mentioning
confidence: 62%
“…An important piece of evidence for the proper description of the one-electron-oxidised form of Ni II -bis(salicylidene)diamine derivatives was recently brought by the group of Stack. [3] Indeed, the X-ray crystallographic data are supportive of a nickel(II) ion bound to a phenoxyl radical. Furthermore, the authors argued that the observed valence tautomeric effect observed in this family of complexes is probably owed to an axial coordination on the metal centre at low temperature.…”
mentioning
confidence: 93%